Factors that influence students' learning discipline during the Covid-19 pandemic for class X SMA NEGERI 3 PEMALANG: Faktor-Faktor yang Mempengaruhi Disiplin Belajar Peserta Didik Di Masa Pandemi Covid-19 Kelas X SMA negeri 3 Pemalang - M ARIF BUDIYANTO (Jurnal Psikoedukasia, 2024)
The aim of this research is to determine the discipline learning level of students during the Covid-19 Pandemic in class X senior high school 3 Pemalang. This type of research uses survey methods with a quantitative approach. The population of this research were all class. The results of the validity test are said to be valid because the learning discipline instrument found that the calculation has a value greater than the table. The learning discipline instrument is also said to be reliable because in the reliability test, the alpha coefficient was found to be greater than 0.600, namely 0.955. In this research, the percentage of internal factors in learning discipline was found to be in the very high category of 9.26%, the percentage in the high category was 20.37%, the percentage in the medium category was 37.04%, and the low category was 4.63%. Meanwhile, for external factors, the percentage for the very high category was 9.26%, the percentage for the high category was 20.37%, the percentage for the medium category was 37.96% and the percentage for the low category was 4.63%. Based on the research that has been carried out, descriptive analysis was used to find out a picture of students' learning discipline. The percentage obtained in the very high category was 6.48%, the percentage in the high category was 25%, the percentage in the medium category was 34.26%, the percentage in the low category amounting to 6.48%. So, the factors that influence the learning discipline of class X students at senior high school 3 Pemalang are internal and axternal factors with the results obtained in the medium category with a percentage of 34.26%. The suggestion that researcher conveys is to conduct similar research with broader targets or even higher levels, so that more optimal results can be found from previous research.